Integrative Model of Guidance and Counseling Services in Islamic Boarding Schools Based on Religious and Applied Psychology: Conceptual Analysis - Agus Handini; Adiansyah (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2026)
Guidance and counseling services in Islamic boarding schools (pesantren) face challenges in responding to the complexity of students' psychological problems because religious approaches and applied psychology are generally still being developed in a partial manner so that there is no conceptual model that integrates the two systematically. This study aims to formulate an integrative model of pesantren guidance and counseling services based on religious approaches and applied psychology through conceptual analysis. The research uses a literature study method with an integrative conceptual analysis approach to 16 research articles published in the 2020–2025 period and systematically selected based on the PRISMA 2020 guidelines. The results of the research produced an integrative model that combines Islamic philosophical foundations, evidence-based psychological principles, service components, implementing actors, pesantren cultural context, change mechanisms, and service outputs in one complete conceptual framework. This model places religious values as a philosophical foundation, while applied psychology serves as a scientific foundation in assessment, intervention, and service evaluation so as to support the spiritual, psychological, social, academic, and character development of students holistically. Thus, the resulting model makes a theoretical contribution to the scientific development of Islamic guidance and counseling as well as a conceptual reference for the development of pesantren guidance and counseling services that are professional, contextual, scientifically tested, and still rooted in Islamic values.